Melanopsin, Photosensitive Ganglion Cells, and Seasonal Affective Disorder - Roecklein, Kathryn A. (2012)
ROECKLEIN, K.A., WONG, P.M., MILLER, M.A., DONOFRY, S.D., KAMARCK, M.L., BRAINARD, G.C. Melanopsin, Photosensitive Ganglion Cells, and Seasonal Affective Disorder…NEUROSCI BIOBEHAV REV x(x) XXX-XXX, 2012. In two recent reports, melanopsin gene variations were associated with seasonal affective disorder (SAD), and in changes in the timing of sleep and activity in healthy individuals. New studies have deepened our understanding of the retinohypothalamic tract, which translates environmental light received by the retina into neural signals sent to a set of nonvisual nuclei in the brain that are responsible for functions other than sight including circadian, neuroendocrine and neurobehavioral regulation. Because this pathway mediates seasonal changes in physiology, behavior, and mood, individual variations in the pathway may explain why approximately 1–2% of the North American population develops mood disorders with a seasonal pattern (i.e., Major Depressive and Bipolar Disorders with a seasonal pattern, also known as seasonal affective disorder/SAD). Components of depression including mood changes, sleep patterns, appetite, and cognitive performance can be affected by the biological and behavioral responses to light. Specifically, variations in the gene sequence for the retinal photopigment, melanopsin, may be responsible for significant increased risk for mood disorders with a seasonal pattern, and may do so by leading to changes in activity and sleep timing in winter. The retinal sensitivity of SAD is hypothesized to be decreased compared to controls, and that further decrements in winter light levels may combine to trigger depression in winter. Here we outline steps for new research to address the possible role of melanopsin in seasonal affective disorder including chromatic pupillometry designed to measure the sensitivity of melanopsin containing retinal ganglion cells.